1948
DOI: 10.1021/ja01187a054
|View full text |Cite
|
Sign up to set email alerts
|

The Steric Inhibition of Resonance. III.1 Acid Strengths of Some Nitro- and Cyanophenols

Abstract: Vol. 70Mass Copolymerization.-The method for determining monomer-polymer composition curves for the five systems reported was essentially the same in each case. Solutions comprising 100 g. of total monomers were prepared by adding appropriate amounts of monomer, comonomer and benzoyl peroxide to 4-oz. French square bottles. The concentrations employed are given in Table I. Air above the monomers was swept out with nitrogen and a metal cap screwed tightly on the bottle mouth. Copolymerizations were carried out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1960
1960
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…In the former series, the most active compound is that of the CH3S02 (III) substituent, while in the later series it is the p-NO¡ substituent. Wheland et al (22) showed that the nitro group in 4-nitro-3,5-xylenol is relatively much less effective in electron-withdrawal (measured = 0.77) than that to be expected by summation of values ( = 1.17). These same investigators found no significant difference between the measured and additive sigma values for 4-cyano-3,5-xylenol ( = 0.79).…”
Section: Discussion Of Resultsmentioning
confidence: 96%
“…In the former series, the most active compound is that of the CH3S02 (III) substituent, while in the later series it is the p-NO¡ substituent. Wheland et al (22) showed that the nitro group in 4-nitro-3,5-xylenol is relatively much less effective in electron-withdrawal (measured = 0.77) than that to be expected by summation of values ( = 1.17). These same investigators found no significant difference between the measured and additive sigma values for 4-cyano-3,5-xylenol ( = 0.79).…”
Section: Discussion Of Resultsmentioning
confidence: 96%
“…4-Cyanophenol has p K a of 7.95. 18 Addition of a second phenyl ring should further decrease the p K a making it plausible that the phenol fragment is partially deprotonated at pH 7.5.…”
mentioning
confidence: 99%
“…The pK a values of 4-nitroand 3,5-dimethyl-phenol (compared with phenol itself) are 2.78 and 0.19, respectively (water, 25°C) 133 . Thus the pK a (calc) value for 4-nitro-3,5-dimethylphenol, assuming strict additivity, is 2.59, compared with pK a (obs) D 1.75, indicating marked steric inhibition of resonance through twisting the NO 2 out of the plane of the ring by the methyl groups.…”
Section: Phenol and Anilinium Ionmentioning
confidence: 93%